Application of the Teams Games Tournament Type Cooperative Learning Model with Domino Card Media to Improve Students' Physics Cognitive Learning Outcomes - Maharani, Aulia Deli; Irawan, Dedi; Ma’aruf, Zuhdi (Journal of Indonesian Science Teachers, 2023)
This research aims to describe the improvement in cognitive learning outcomes of students at SMA Negeri 6 Pekanbaru on optical instruments through the application of the TGT (Teams Games Tournament) type cooperative learning model in the form of domino cards. The type of research used is Quasi-Experimental. The research sample consisted of 35 students from class XI MIPA 3 as the control class and 36 students from class XI MIPA 4 as the experimental class. The instrument in this research is a written test on optical instruments, totaling 25 objective questions. The cognitive learning results of students by comparing the average scores of the experimental class and the control class obtained an average of 81.11 with a very high category in the experimental class while an average of 63.20 with a medium category in the control class. Overall, it can be concluded that the TGT-type cooperative learning model in the form of card media can improve the physics cognitive learning outcomes of class XI students at SMA Negeri 6 Pekanbaru.